Khazanah Tasawuf Nusantara: Tarekat Naqsyabandiyyah Khalidiyyah di Malaysia - Muhammad Faiz (Institut Ilmu Keislaman Annuqayah, 2016)
Sufism as one of the three essential elements of knowledge in Islam, in addition to tawhid (aqi>dah) and jurisprudence (syari>’a), is a treasure of Islamic civilization playing an important role in spreading the values ​​of Islam throughout the world. Through sufism doctrine, Islam able to enter and thrive in the Nusantara. Nonetheless, scornful views towards sufism could not be avoided, specifically about the practice of tariqa (sufi path) that teaches concepts such as bai'at, z, rabitah, tawassul, sala>wa>t, etc. Some people perceive sufism and tariqa as heresy and despicable deeds. This study will discuss the history of sufism and tariqa focusing on the emergence and development, also the position, role, and importance of tariqa. Besides these problems, tariqa in the Nusantara will also be studied, specifically about the Naqshabandiyyah Khalidiyyah in Malaysia. The method of this study is literature review about sufism and tariqa, especially references that discuss the Naqsyabandiyyah Khalidiyyah in Malaysia. This study concludes that Naqsyabandiyyah Khalidiyyah is the most popular and widespread tariqa in Malaysia, which entered the Malay Peninsula through two main paths: Mecca and Sumatera. This tariqa is well received by people because it provides the teaching and guidance to bring people closer to Allah in order to be the perfect man (al-insan al-kamil) on the basis of syari>’a.",